The Contribution of Human Rights in Thinking on Renewing The Book of Law of Criminal Events (KUHAP) - Yahyanto Yahyanto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2019)
The fundamental principle of human rights is that all people are born free and have equality in human rights. Equality requires equal treatment; it means that anyone should be treated equally in any condition before the law. The idea of Human Rights in the Draft of the Law on Criminal Procedure Code, which will be upheld, will become a new legalized law in the future, not apart from lifting and placing a suspect, defendant, and convicted dignified position as a creature of God. Moreover, in the end, declarative human rights principles will not mean much if the stage of the rule of law does not follow them.Fundamental dari hak asasi manusia adalah ide yang meletakkan semua orang terlahir bebas dan memiliki kesetaraan dalam hak asasi manusia. Kesetaraan mensyaratkan adanya perlakuan yang setara, dimana pada situasi sama harus diperlakukan dengan sama, dimana pada situasi yang berbeda diperlakukan dengan berbeda pula. Pemikiran HAM dalam RUU KUHAP yang akan diundangkan menjadi UU kedepan, tidak terlepas mengangkat dan menempatkan seorang tersangka, terdakwa dan terpidana dalam kedudukan yang bermartabat sebagai makhluk ciptaan Tuhan. Dan pada akhirnya, prinsip-prinsip HAM yang bersifat deklaratif tidak akan banyak berarti apabila tidak diikuti dengan tahap supremasi hukum.